2016
DOI: 10.4103/1735-1995.196611
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of celiac axis, superior mesenteric artery, and hepatic artery: Evaluation with multidetector computed tomography angiography

Abstract: Background:The celiac axis, superior mesenteric artery (SMA), and hepatic artery are the most important branches of abdominal aorta due to their vascularization field. The aim of our study was to evaluate the prevalence of different anatomical variation of celiac axis, SMA, hepatic artery, and its branches with multidetector computed tomography (MDCT) angiography of upper abdomen arteries.Materials and Methods:MDCT of 607 kidney donor and traumatic patients that referred to MDCT unit at Al Zahra Hospital in Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 19 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…There was no significant difference between males and females in terms of CeT and CHA variations (35.3%, 35.9%, respectively). ry or replaced vessels [6,7]. The importance of CeT and CHA is regarded as their vascularisation which is crucial for interventional and surgical procedures like liver transplantation and surgical preoperative planning [8,15].…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference between males and females in terms of CeT and CHA variations (35.3%, 35.9%, respectively). ry or replaced vessels [6,7]. The importance of CeT and CHA is regarded as their vascularisation which is crucial for interventional and surgical procedures like liver transplantation and surgical preoperative planning [8,15].…”
Section: Resultsmentioning
confidence: 99%
“…Cadaver, imaging, and liver transplantation studies have reported celiac trunk trifurcation in 85.1%, 89.6%, and 95.4%, respectively [ 8 ]. In contrast, cadaveric studies by Chitra [ 9 ], Nelson et al [ 15 ], Mburu et al [ 16 ], and Farghadani [ 17 ] reported trifurcated celiac trunk prevalences of 40%, 60%, 61.8%, and 63.6%, respectively. In our study, the false tripod of the celiac trunk was present in 36.4% (51/140), which predominated over the true form of the celiac trunk (7.1%, 10/140).…”
Section: Discussionmentioning
confidence: 97%
“…In a study with 607 kidney donors and trauma patients, it was observed that 388 (63.9%) had a classic arterial pattern, whereas 219 (36.1%) presented some type of variation. Among the observed changes, one variation was more common than others, in which the SMA originated the right hepatic artery in 58 (9.6%) of the cases 2 .…”
Section: Introductionmentioning
confidence: 95%